(NsTACIONARNYE SLU^AJNYE PROCESSY (B/s - (NrOZANOW(B, (N`RIJ aNATOLXEWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1990)
(NbIBLIOGR(B.: (NS(B. 267-271s
Keywords: (NsLU^AJNYE PROCESSY (B((NMAT(B.), (NTEORIQs